Desalination effects on macroalgae (part b): Transplantation experiments at brine-impacted sites with Dictyota spp. from the Pacific Ocean and Mediterranean Sea - Muñoz, Pamela T.; Rodríguez-Rojas, Fernanda; Celis-Plá, Paula S. M.; López-Marras, Américo; Blanco-Murillo, Fabio; Sola, Iván; Lavergne, Céline; Valenzuela, Fernando; Orrego, Rodrigo; Sánchez-Lizaso, José Luis; Sáez, Claudio A. (Frontiers in Marine Science, 2023)
Desalination residual brines are mostly discharged to marine environments, which can produce osmotic stress on sensitive benthic organisms. In this investigation, we performed transplantation experiments nearby desalination plants using two brown macroalgae species from a cosmopolitan genus: Dictyota kunthii (Chile) and Dictyota dichotoma (Spain). Parameters related to photosynthetic activity and oxidative stress were evaluated at 3 and 7 days for D. kunthii, and 3 and 6 days for D. dichotoma; each at 2 different impacted sites and 1 control. We observed that brine exposition at both impacted sites in Chile generated a marked stress response on D. kunthii, reflected in a decrease of primary productivity (ETRmax), light requirement (EkETR), and an excessive thermal dissipation (NPQmax), especially at 7 days. In D. dichotoma, similar impaired photosynthetic activity was recorded but only at the highest brine influence site during day 3. Regarding oxidative stress, both species displayed high levels of H2O2 when exposed to brine-influenced sites. Although in D. kunthii H2O2 content together with lipid peroxidation was higher after 3 days, these returned to baseline values towards day 7; instead, D. dichotoma H2O2 levels increased only at day 6. This easy and practical approach has proven to provide valuable data to address potential impacts of brine discharges at global scale coastal ecosystems.